Pengendalian Diri sebagai Kebajikan Moral dalam Krisis Seksualitas Kontemporer menurut Kitab Sirakh 5:2 (Jurnal Pendidikan Agama dan Teologi, 2025)
Social changes driven by globalization and advancements in digital technology have led to a shift in the values surrounding human sexuality, from being sacred to becoming increasingly liberal and permissive. This phenomenon has triggered an identity crisis, particularly among the younger generation. This study aims to explore the meaning of self-control as presented in Sirach 5:2 and to evaluate its relevance as an ethical and theological foundation in addressing the contemporary crisis of sexuality. The method employed is a literature study using a qualitative-theological approach and textual analysis of Sacred Scripture. The findings indicate that self-control in Sirach 5:2 is not merely the suppression of desire but an expression of moral and spiritual maturity grounded in wisdom and divine grace. In light of Christian ethics, this virtue shapes responsibility, chastity, and fidelity within human relationships. Thus, self-control becomes a fundamental basis for building personal integrity and a dignified direction of life amidst a permissive cultural current.